Higher Education Case Management Amid COVID-19: Toward Holistic Student Self-Assessment to Allocate Emergency Resources on Campus. Issue 4 (3rd April 2021) - Black, Lisa; Taylor, Z. W.
ABSTRACT: Although case management in higher education is a relatively new phenomenon, the challenges presented by COVID-19 have forced many institutions to deliver emergency services in an extremely rapid fashion and adopt case management strategies to serve students in crisis. This case study shares how one large community college system developed a one-to-one (1–1) case management protocol prior to COVID to allow students to self-assess their needs to distribute emergency aid and resources in a personalized, contextualized, and resource-sensitive fashion. This study will introduce the case management protocol and student self-assessment as well as provide community college practitioners with the opportunity to adapt the model and the assessment to individual institutional contexts. Implications for research, practice, and policy will be addressed, in addition to providing practitioners resources for case management systems development.